Graded chronic noncancer pain distribution using the Graded Chronic Pain Scale-Revised framework: a cross-sectional study - Sophie Sell Hellmann; Ola Ekholm; Gitte Handberg; Pernille Lykke Petersen; Geana Paula Kurita; Per Sjøgren; Lau Caspar Thygesen; Henrik Bjarke Vaegter (PAIN Reports)
Abstract. Introduction:. Chronic noncancer pain affects approximately one-fourth in population-based studies calling for more nuanced insights by applying the Graded Chronic Pain Scale-Revised (GCPS-R) framework for classifying graded chronic noncancer pain distribution in national disease surveillance. Objectives: The GCPS-R framework was included in the comprehensive questionnaire repeatedly used in the Danish National Health and Morbidity Surveillance program to provide more distinct measures for chronic non-malignant pain disease manifestation in Denmark. Methods:. A cross-sectional study inviting randomly 25,000 adults 16 years and older to self-report questionnaires comprising the GCPS-R framework as part of the nationwide Danish National Health Survey 2023. Prevalences (%) and multivariate-adjusted odds ratios (ORs) with 95% confidence intervals (95% CI) by ordinal logistic regression were calculated for GCPS-R by sex, area of living, age, country of origin, socioeconomic factors, body mass index, and Charlson Comorbidity Index. Results:. The prevalence of chronic noncancer pain was overall 28.1% (95% CI 27.2%–29.0%) in 8,643 included individuals without cancer diagnosis counting 7.4% (6.9%–8.0%) with mild-impact, 7.1% (6.6%–7.6%) with bothersome-impact, and 13.6% (12.9%–14.4%) with high-impact chronic noncancer pain. Women had 66% (odds ratio (OR) 1.66; 95% CI 1.50–1.84) elevated odds of more severely graded chronic noncancer pain referenced to men. Socioeconomic factors influenced odds inversely. Body mass index was related to GCPS-R by dose-response effects of more than doubled elevated odds in World Health Organization obese class II (2.42; 1.92–3.06) and obese class III (4.43; 3.30–5.93) referenced to normal body mass index individuals. Comorbidity elevated odds of more severely graded chronic noncancer pain by 86% (1.86; 1.57–2.19) referenced to individuals without comorbidity. Conclusions:. More than one-quarter individuals reported chronic noncancer pain characterized particularly by high-impact graded chronic noncancer pain when applying the GCPS-R framework for classifying graded chronic noncancer pain distribution in national disease surveillance for rational health care administration.